(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
Criminal policy prevails mainly in the field of legislation. Judicial power is an independent power; judges are only subject to the laws. Economic policy is more practical than science, although it has a theoretical background for applied economics. It can be defined as the state’s active intervention in the economy, a conscious, coherent and targeted action that affects production, consumption, and exchange and capital formation. The relationship between economic policy and criminal policy in the area of combating economic crime can be characterized by the fact that criminality policy should be more in keeping with economic policy considerations than vice versa. Badly elected criminal policy does not necessarily help the development of the economy, economic policy and criminal policy considerations need to be carefully coordinated. In this essay we will examine the relationship between the economic policy and the criminal policy in the light of the new anti-money laundering and counter-terrorist financing regulation.